2006
DOI: 10.1111/j.1469-7580.2006.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Total sleep deprivation inhibits the neuronal nitric oxide synthase and cytochrome oxidase reactivities in the nodose ganglion of adult rats

Abstract: Sleep disorders are a form of stress associated with increased sympathetic activity, and they are a risk factor for the occurrence of cardiovascular disease. Given that nitric oxide (NO) may play an inhibitory role in the regulation of sympathetic tone, this study set out to determine the NO synthase (NOS) reactivity in the primary cardiovascular afferent neurons (i.e. nodose neurons) following total sleep deprivation (TSD). TSD was performed by the disc-onwater method. Following 5 days of TSD, all experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 67 publications
0
29
0
1
Order By: Relevance
“…Sleep deprivation can contribute directly to blood pressure dysregulation via increased sympathetic nervous system and adrenocortical excitation independent of sleep apnea. For example, experimentally induced sleep deprivation increases blood pressure and inhibits neuronal nitric oxide synthase in nodose neurons in rats [17]. The authors suggest that reduced expression of nitric oxide synthase in primary cardiovascular neurons could increase the sympathetic nervous system tone and potentially increase the risk for essential hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…Sleep deprivation can contribute directly to blood pressure dysregulation via increased sympathetic nervous system and adrenocortical excitation independent of sleep apnea. For example, experimentally induced sleep deprivation increases blood pressure and inhibits neuronal nitric oxide synthase in nodose neurons in rats [17]. The authors suggest that reduced expression of nitric oxide synthase in primary cardiovascular neurons could increase the sympathetic nervous system tone and potentially increase the risk for essential hypertension.…”
Section: Introductionmentioning
confidence: 98%
“…With the coming of industrialization, sleep disorders are increasingly becoming a major public health issue, affecting millions of people in many countries (Malik & Kaplan, 2005;Lenfent, 2006). In subjects suffering sleep deprivation there is a desynchronization of cellular function, which unavoidably leads to metabolic disturbances (McEwen, 2006;Chang et al 2006). Recent biochemical and physiological studies have indicated that chronic sleep deprivation is an important factor in neurobehavioral, cardiovascular and metabolic morbidity in both developing and adult patients (Copinschi, 2005;Kheirandish & Gozal, 2006;Thase, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm demonstrado que a síndrome metabólica [5][6][7][8] está associada ao aumento da morbimortalidade e que também está associada ao aumento do cortisol e intolerância a glicose. Pesquisas têm demonstrado que a diminuição ou privação de sono, em humanos, envolvem alterações metabólicas, problemas na regulação do apetite e diminuição do dispêndio de energia, tornando-se fator de risco para o desenvolvimento de várias doenças tais como doenças cardiovasculares, obesidade, resistência a insulina, intolerância a glicose, dislipidemia e hipertensão e manifestações que alteram a regulação de energia 5,[9][10][11][12][13][14] . Em animais, o estresse pode ser provocado por privação de sono, que por sua vez, ativa o eixo hipotalâmico-pituitário-adrenal 15 .…”
Section: Abstract Objectiveunclassified